Determinants of tap water mistrust among Phoenix, Arizona Latinx adults - Abigail T. Colburn; Matthew P. Buman; Amber Wutich; Sonia Vega-López; Punam Ohri-Vachaspati; Stavros A. Kavouras (IWA Publishing, 2023)
The purpose of this investigation was to characterize factors that predict tap water mistrust among Phoenix, Arizona Latinx adults. Participants (n = 492, 28 ± 7 years, 37.4% female) completed water security experience-based scales and an Adapted Survey of Water Issues in Arizona. Binary logistic regression determined odds ratios (OR) with 95% confidence intervals (95% CI) for the odds of perceiving tap water to be unsafe. Of all participants, 51.2% perceived their tap water to be unsafe. The odds of mistrusting tap water were significantly greater for each additional favorable perception of bottled compared to tap water (e.g., tastes/smells better; OR = 1.94, 95% CI = 1.50, 2.50), negative home tap water experience (e.g., hard water mineral deposits and rusty color; OR = 1.32, 95% CI = 1.12, 1.56), use of alternatives to home tap water (OR = 1.25, 95% CI = 1.04, 1.51), and with decreased water quality and acceptability (OR = 1.21, 95% CI = 1.01, 1.45; P < 0.05). The odds of mistrusting tap water were significantly lower for those whose primary source of drinking water is the public supply (municipal) (OR = 0.07, 95% CI = 0.01, 0.63) and with decreased water access (OR = 0.56, 95% CI = 0.48, 0.66; P < 0.05). Latinx mistrust of tap water appears to be associated with organoleptic perceptions and reliance on alternatives to the home drinking water system. HIGHLIGHTS Over half of the Latinx participants believe that their tap water is not safe to drink.; Latinx adults' mistrust of tap water appears to be related to negative perceptions of tap water, such as unpleasant smell and taste.; Latinx adults who mistrust their tap water appear to rely on bottled water and gallon containers for drinking water as alternatives to tap water.;